2022
DOI: 10.1002/ajp.23423
|View full text |Cite
|
Sign up to set email alerts
|

External environmental conditions impact nocturnal activity levels in proboscis monkeys (Nasalis larvatus) living in Sabah, Malaysia

Abstract: Recently, several diurnal nonhuman anthropoids have been identified displaying varying degrees of nocturnal activity, which can be influenced by activity "masking effects"-external events or conditions that suppress or trigger activity, temporarily altering normal activity patterns. Environmental masking characteristics include nocturnal temperature, rainfall, cloud cover, and moon brightness. Similarly, other ecological characteristics, including proximity to humans and predators and daytime activity, may als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…This means that sleeping site selection may have an important influence on their fitness (Feilen & Marshall, 2014), especially considering that primates reportedly spend up to half of their lives at sleeping sites (Anderson, 1998). Sleeping site selection in primates is strongly influenced by factors linked to safety from predators (Li et al ., 2010; Bernard et al ., 2011; Feilen & Marshall, 2014; Mochida & Nishikawa, 2014; Thiry et al ., 2016; Nunn & Samson, 2018; Reinhardt, 2020), weather conditions (Li et al ., 2010; Reyes et al ., 2021; Kooros et al ., 2022) and social behaviour (Anderson, 1998, 2000; Li et al ., 2010; Mochida & Nishikawa, 2014). Furthermore, it has already been described that water level (Matsuda et al ., 2010) and the presence of mosquitoes influence sleeping site selection (Feilen & Marshall, 2014, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that sleeping site selection may have an important influence on their fitness (Feilen & Marshall, 2014), especially considering that primates reportedly spend up to half of their lives at sleeping sites (Anderson, 1998). Sleeping site selection in primates is strongly influenced by factors linked to safety from predators (Li et al ., 2010; Bernard et al ., 2011; Feilen & Marshall, 2014; Mochida & Nishikawa, 2014; Thiry et al ., 2016; Nunn & Samson, 2018; Reinhardt, 2020), weather conditions (Li et al ., 2010; Reyes et al ., 2021; Kooros et al ., 2022) and social behaviour (Anderson, 1998, 2000; Li et al ., 2010; Mochida & Nishikawa, 2014). Furthermore, it has already been described that water level (Matsuda et al ., 2010) and the presence of mosquitoes influence sleeping site selection (Feilen & Marshall, 2014, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that proboscis monkeys are assumed to be solely diurnal primates (Matsuda et al, 2009a), they show some activity throughout the night. For example, using accelerometery collars, Kooros et al (2022) showed that at night, proboscis monkeys engaged in between 3.5 and 8.5% of their daylight activity level, and that this activity depended on a variety of factors like diurnal activity, rainfall and temperature. Because our primary target behaviour, R/R, cannot be detected by measures that indicate whole-body animal movement, the present study relies on nighttime video footage recorded in the natural environment of the species.…”
Section: Introductionmentioning
confidence: 99%